Analisis Teknik Penerjemahan Kaidah Nahwu ke dalam Bahasa Indonesia oleh Mahasiswa Pba - Fina Nur Fadhilah; M. Ja'far Shodiq; Kristina Imron (EL-IBTIKAR: Jurnal Pendidikan Bahasa Arab, 2023)
In translation activities, a basis is needed in the form of translation techniques for translators to produce products or works of translation from the source language to the target language. Accurate translation results can be achieved by using techniques appropriate to the source text to be translated into the target language. This study aims to find out what translation techniques are used by PBA students in translating nahwu rules into Indonesian. The method used in this research is descriptive qualitative research method. The results of the analysis of the translation of the nahwu rules from Arabic to Indonesian were carried out by 1st semester Arabic Language Education students at UIN Raden Fatah, It can be concluded that of the 18 translation techniques proposed by Molina and Albir, 5 forms of techniques were identified, namely borrowing, literal translation, reduction, generalization, and linguistic amplification techniques. Of the five techniques, student translation results are dominated by literal translation techniques and borrowing techniques.order.